2019
DOI: 10.1093/mnras/stz3566
|View full text |Cite|
|
Sign up to set email alerts
|

Spectral energy distributions of candidate periodically variable quasars: testing the binary black hole hypothesis

Abstract: Periodic quasars are candidates for binary supermassive black holes (BSBHs) efficiently emitting low frequency gravitational waves. Recently, ∼150 candidates were identified from optical synoptic surveys. However, they may be false positives caused by stochastic quasar variability given the few cycles covered (typically 1.5). To independently test the binary hypothesis, we search for evidence of truncated or gapped circumbinary accretion disks (CBDs) in their spectral energy distributions (SEDs). Our work is m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 168 publications
(226 reference statements)
0
9
0
Order By: Relevance
“…All four candidate periodic quasars show similar SEDs (within 3σ) to those of the control quasars. Guo et al (2020) have studied the SEDs of the periodic quasar candidates discovered by Graham et al (2015a) and Charisi et al (2016). They have found that the SEDs of periodic quasar candidates from the CRTS and PTF studies are consistent with those of the control quasars.…”
Section: Spectral Energy Distributionmentioning
confidence: 89%
“…All four candidate periodic quasars show similar SEDs (within 3σ) to those of the control quasars. Guo et al (2020) have studied the SEDs of the periodic quasar candidates discovered by Graham et al (2015a) and Charisi et al (2016). They have found that the SEDs of periodic quasar candidates from the CRTS and PTF studies are consistent with those of the control quasars.…”
Section: Spectral Energy Distributionmentioning
confidence: 89%
“…To estimate the host-galaxy stellar mass (see Section 3.2 below for details), we queried the archival SED data for DES J0218−0430 using the Vizier tool 5 within 3 arcsec following the procedures of Guo et al (2020a). We adopt measurements from large systematic surveys to focus on a more homogeneous data set.…”
Section: Multiwavelength Observationsmentioning
confidence: 99%
“…a lower limit of ∼10% for the other candidate periodic quasars from the literature which are radio-loud (𝑅 >10). Guo et al (2020) has carried out a multi-wavelength SED study for the previous candidate periodic quasars from the CRTS and the PTF. These authors find a tentatively higher fraction of radio-loud quasars compared to the control sample of ordinary quasars matched in redshift and luminosity.…”
Section: Comparison To Previous Candidate Periodic Quasarsmentioning
confidence: 99%